The Implementation of Gender-Responsive Fiqh: A Study of Model Application of Women-Friendly and Child Care Village in Post-Covid-19 Pandemic - Ahmad Muhtadi Anshor; Muhammad Ngizzul Muttaqin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Amid the gender-responsive movement, this study addresses issues in Islamic jurisprudence (fiqh). This is because fiqh products appear unable to address contemporary issues, particularly those affecting women and children. The frequent sexual and domestic abuse and women's slower acceleration than men are some of the issues women face today. Meanwhile, the current children in Indonesia are also experiencing various pressures due to the many problems of violence against them. Worse yet, when Indonesia encounters health problems and the severity of Covid-19, Indonesia also faces the problem of women’s and children’s welfare. To overcome this problem, the Ministry of Women's Empowerment and Child Protection (Kemen PPPA) and the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendesa PDTT) have declared a Movement to Increase Women's Involvement through Women-Friendly and Child-Care Village. After the Covid-19 emergency, this movement is one of the synergistic efforts to achieve every town's Sustainable Development Goals (SDGs). This study of Islamic law is classified as a reaction to societal issues. Focusing on literature studies, this study finds that implementing women-friendly and child-care villages represent the responsive ijtihad fiqh methodology support in developing fiqh towards gender responsiveness.